Model Contextual Teaching Learning dan Kemampuan Penalaran Matematis Siswa SMP Singingi pada Materi Aritmatika - Nur atira; Hasanuddin (CONSISTAN (Jurnal Tadris Matematika), 2025)
This research assesses the effectiveness of the Contextual Teaching and Learning (CTL) model in enhancing students' understanding of social arithmetic and its effect on their mathematical reasoning skills. The study was conducted with 20 students from class VII at SMP Negeri Singgi using a descriptive qualitative approach. The findings indicated that students' mathematical reasoning skills were still low, with only five out of 20 students meeting or exceeding the Minimum Completion Criteria (KKM). The average mathematical reasoning ability in the class was also below expectations. Interviews with teachers revealed challenges in implementing CTL, particularly concerning time limitations and the complexity of the material. While CTL makes learning enjoyable, it requires collaborative efforts to assess and refine teaching strategies and optimize the model. Continuous evaluation and adaptation of teaching strategies, along with collaboration among teachers, students, and relevant stakeholders, are crucial for improving the mathematics learning outcomes at SMP Negeri Singgi. The results of this study contribute to the development of more contextual and life-relevant mathematics teaching approaches.